Охота на мужа, или Заговор проказниц: [роман] / Юлия Шилова - Шилова Юлия Витальевна (Час криминала, 2003)
Экземпляры: Аб (20141029) / Инвентарный номер: 101715 / Цена: 60.00 / Авт.знак: Ш 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6